2002
DOI: 10.1021/jo020442o
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Reduction of a Chiral N-Boc-Protected δ-Amino-α,β-unsaturated γ-Keto Ester Phe-Gly Dipeptidomimetic

Abstract: The readily available N-Boc-protected delta-amino alpha,beta-unsaturated gamma-keto ester 1 was diastereoselectively reduced to the corresponding alcohols 2 and 3, using boron- and aluminum-based reducing reagents. Reduction reactions were successful and resulted in anti/syn ratios of alcohols of >95:5 (80% yield), using LiAlH(O-t-Bu)(3) in EtOH at -78 degrees C under chelation control, and 5:95 (98% yield), using NB-Enantride in THF at -78 degrees C under Felkin-Anh control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…18 In short, ketomethylene derivative 5 14 was first diastereoselectively reduced to the respective alcohol, followed by protective group manipulations and separation of diastereomeric mixtures. Diastereoselective reduction of ketomethylene derivative 5 14 was performed using conditions guided by the work of Hoffman et al 19 and Våbenø et al 20 (Scheme 1). Treatment of 5 with LiAlH(O-tBu) 3 in EtOH 19,20 gave alcohol 6 in 75% yield and with an excellent diastereomeric ratio (dr) 4S : 4R of 1 : 99 according to 1 H NMR analysis.…”
Section: Synthesismentioning
confidence: 99%
“…18 In short, ketomethylene derivative 5 14 was first diastereoselectively reduced to the respective alcohol, followed by protective group manipulations and separation of diastereomeric mixtures. Diastereoselective reduction of ketomethylene derivative 5 14 was performed using conditions guided by the work of Hoffman et al 19 and Våbenø et al 20 (Scheme 1). Treatment of 5 with LiAlH(O-tBu) 3 in EtOH 19,20 gave alcohol 6 in 75% yield and with an excellent diastereomeric ratio (dr) 4S : 4R of 1 : 99 according to 1 H NMR analysis.…”
Section: Synthesismentioning
confidence: 99%
“…A similar situation has also been observed in other allylic alcohols derived from phenylalanine. 35 From the chemical shift of this diagnostic proton it was thus possible to assign the S,R and S,S configurations to the major and minor isomers of alcohols 17a,b, respectively. …”
Section: S2mentioning
confidence: 99%
“…Alternatively, the same result could be explained with a Felkin-Anh model in which NHBoc is the medium group and benzyl is the large group 32 ( Figure 4b). Based on calculations of the volume of the two groups, it has been recently suggested that NHBoc is larger than benzyl; 35 however, the bulky t-butyl group of NHBoc is four bonds away from the reaction center, to which it is connected by a linear, and relatively small, array of atoms. Thus the effectiveness of NHBoc in shielding the carbonyl from attack by the nucleophile may be overestimated by these calculations.…”
Section: Scheme 2 Synthesis Of Epoxyalcohol Inhibitorsmentioning
confidence: 99%
“…Conversion of the ketone to the hydroxy group via selective reduction to either of the two diastereoisomers is easily achieved according to literature procedures. [15,16] While coupling reactions of the type described above proved to be successful with a variety of amino acids, they were limited only to reactions of thioesters derived from amino acids, and attempts to extend the method to other substrates were not successful. Furthermore, some amino acids also proved to be problematic, with bulky amino acid side chains, such as with valine, and N-Boc protection being poorly tolerated.…”
Section: General Introductionmentioning
confidence: 99%